Widowmaker - Doiron, Paul (Doiron, Paul. Mike Bowditch mysteries., 2016)
"When a mysterious woman in distress appears outside his home, Mike Bowditch has no clue she is about to blow his world apart. Amber Langstrom is beautiful, damaged, and hiding a secret with a link to his past... She claims her son Adam is a wrongfully convicted sex offender who has vanished from a brutal work camp in the high timber around the Widowmaker Ski Resort. She also claims that Adam Langstrom is the illegitimate son of Jack Bowditch, Mike's dead and diabolical father. He is the half-brother Mike never knew he had. After trying so hard to put his troubled past behind him, Mike is reluctant to revisit the wild country of his childhood and again confront his father's history of violence. But Amber's desperation and his own need to know the truth make it hard for him to refuse her pleas for help. In search of answers, Bowditch travels through a mountainous wilderness to a place hidden from the rest of the world, where the military guards a top-secret interrogation base, sexual predators live together in a backwoods colony, and self-styled vigilantes are willing to murder anyone they consider their enemies. Mike Bowditch must exorcise the demons of the past before the real-life demons of the present kill him first"--